New Zealand : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 1999)
This 1999 Article IV Consultation highlights that economic performance of New Zealand improved during the 1990s. Inflation averaged about 2 percent, compared with nearly 10 percent in the 1980s, while economic growth also picked up. Despite these improvements, the current account deficit remains high, increasing the economy's vulnerability to external shocks. Although growth performance has improved, most estimates suggest that the potential growth rate remains too low to close the per capita income gap between New Zealand and the advanced-economy average.